(untitled) (Clinics, 2016)
OBJECTIVES: Bone marrow adipose tissue has been associated with low bone mineral density. However, no data exist regarding marrow adipose tissue in primary hyperparathyroidism, a disorder associated with bone loss in conditions of high bone turnover. The objective of the present study was to investigate the relationship between marrow adipose tissue, bone mass and parathyroid hormone. The influence of osteocalcin on the homeostasis model assessment of insulin resistance was also evaluated. METHODS: This was a cross-sectional study conducted at a university hospital, involving 18 patients with primary hyperparathyroidism (PHPT) and 21 controls (CG). Bone mass was assessed by dual-energy x-ray absorptiometry and marrow adipose tissue was assessed by 1H magnetic resonance spectroscopy. The biochemical evaluation included the determination of parathyroid hormone, osteocalcin, glucose and insulin levels. RESULTS: A negative association was found between the bone mass at the 1/3 radius and parathyroid hormone levels (r = -0.69; p